Increasing the Competency of Teachers in Disaster Prone Areas in Kenegerian Sihotang, Harian District, Samosir Regency - Sihotang, Hotmaulina; Nadeak, Bernadetha; Simbolon, Bintang; Sinaga, Dameria; Samaloisa, Benhur (Asian Journal of Community Services, 2024)
UKI carries out community service as an implementation of knowledge to help society. The horror of Sihotang which experienced a disaster. Community service activities in the form of counseling motivate students to have goals and study seriously to achieve their goals. Apart from that, Community service is carried out in the form of training for teachers which aims to improve pedagogical competence, personal competence, social competence and professional competence in order to produce graduates who will become the next generation with their character. There were 204 students who took part in counseling and 65 teachers who took part in training. Community service activities were carried out in collaboration with UKI and the Samosir Regency Education, Youth and Sports Department. The results of community service provide enthusiasm, happiness and increase teacher competence.